Correlation Between Conventional Theory and Islamic Economic Thought - Novita, Dwi; Asnaini, Asnaini; Putra, Haris Maiza (Madania: Jurnal Kajian Keislaman, 2023)
This study discusses conventional economic theory, Islamic economic thought, and its correlation or relationship. Conventional economics views worldly life as an absolute right for humans, while Islamic economics teaches that worldly life is based on the principle of accountability to Allah SWT. Because of this difference, location of the difference is presented in this paper. This research is library research, conducted by analyzing and interpreting the theoretical matters related to the research. The results showed that; First, conventional economics is an economic theory related to "freedom" to move towards a free market and the economic system understands free trade in the era of globalization which aims to eliminate protectionism economic policies. Second, Islamic economics is a science that seeks to see, study, research, and finally solve economic problems in an Islamic way. Third, is the correlation between conventional economic theory and Islamic economic thought; conventional economics views science as something secular, while Islamic economics is based on religious principles. The research findings also show that the basic differences lie in differences in principles, differences in market mechanisms, differences in wealth distribution, differences in profits, differences in objectives, and differences in the concept of ownership. Penelitian ini membahas tentang teori ekonomi konvensional, pemikiran ekonomi Islam, dan korelasi atau keterkaitannya. Ilmu ekonomi konvensional memandang kehidupan duniawi sebagai hak mutlak bagi manusia, sedangkan ekonomi Islam mengajarkan bahwa kehidupan duniawi didasarkan pada prinsip pertanggungjawaban kepada Allah SWT. Karena perbedaan tersebut, lokasi perbedaannya disajikan dalam makalah ini. Penelitian ini merupakan penelitian kepustakaan, yang dilakukan dengan menganalisis dan menafsirkan hal-hal teoritis yang berkaitan dengan penelitian. Hasil penelitian menunjukkan bahwa; Pertama, ekonomi konvensional merupakan teori ekonomi yang berkaitan dengan “kebebasan” untuk bergerak menuju pasar bebas dan sistem perekonomiannya memahami perdagangan bebas di era globalisasi yang bertujuan untuk menghilangkan kebijakan ekonomi proteksionisme. Kedua, ekonomi Islam merupakan ilmu yang berupaya melihat, mengkaji, meneliti, dan akhirnya menyelesaikan permasalahan perekonomian dengan cara Islami. Ketiga, korelasi teori ekonomi konvensional dengan pemikiran ekonomi Islam; ilmu ekonomi konvensional memandang ilmu pengetahuan sebagai sesuatu yang sekuler, sedangkan ilmu ekonomi Islam didasarkan pada prinsip-prinsip agama. Temuan penelitian juga menunjukkan bahwa perbedaan mendasar terletak pada perbedaan prinsip, perbedaan mekanisme pasar, perbedaan distribusi kekayaan, perbedaan keuntungan, perbedaan tujuan, dan perbedaan konsep kepemilikan.